Enhancing Self-Regulated Learning through Task-Based Language Teaching in English Speaking among Pre-Service Teachers - Faidah Yusuf; Ahmad Ardillah Rahman (Universitas Pendidikan Ganesha, 2026)
This study addresses the limited research on the relationship between Task-Based Language Teaching (TBLT) and self-regulated learning (SRL) among pre-service teachers, despite the importance of SRL in supporting independent English learning. This mixed-methods study aims to examine how TBLT contributes to the development of SRL in English-speaking courses. Quantitative data were collected from 117 first-year students enrolled in bilingual classes at Universitas Negeri Makassar, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). To complement the findings, semi-structured interviews were conducted with eight selected participants. The results indicate that responsibility and initiative are the most significant predictors of SRL, suggesting that students are more likely to regulate their learning when tasks require active engagement and personal accountability. In contrast, understanding of materials, evaluation, and reflection show positive but non-significant effects. Qualitative findings support these results, revealing that task-based activities promote time management, goal setting, and independent learning behaviors. However, reflection practices were often informal and lacked structured guidance, which may explain their limited contribution to SRL. These findings suggest that TBLT can effectively enhance SRL when tasks are designed to promote responsibility, initiative, and structured reflection. The study highlights the importance of autonomy-supportive task design and guided reflective practices in fostering self-regulated learning among pre-service teachers.